Clinical Correlation of Chronic Rhinosinusitis with Nasal Polyps - Verma, Lok Ram; Sharma, Anshu (Journal of Nepalgunj Medical College, 2019)
Background: Chronic rhino sinusitis with and without nasal polyps represent different group of one chronic inflammatory disease of the mucosa of the nasal cavity and paranasal sinuses. Coexistence of chronic rhinosinusitis with nasal polyps’ has similar characteristics of inflammation that supports assumption that chronic rhinosinusitis and nasal polyps may at least be in part, the same disease process. Objectives: This study is aimed to correlate the chronic rhinosinusitis associated with nasal polyps. Methods: This was a prospective descriptive study was conducted on the patients attending the department of ENT in NGMC teaching hospital from March 2016 to September 2017. Result: There were 70 cases including 47male and 23 female, with an age range of 17 years to 65 years. Conclusion: This study supports that a patient with chronic rhinosinusitis associated with nasal polyps is a subtype of chronic sinus disease.